High-dose intravenous immunoglobulin may be an efficient treatment option for patients with late-onset high-grade immune effector cell-associated hematotoxicity refractory to standard therapies - Yousef Laham; Shimrit Ringelstein-Harlev; Daniel Kurnik; Riva Fineman; Dana Yehudai-Ofir; Lilach Bonstein; Noga Setter-Marco; Eyal Braun; Itai Ghersin; Tsila Zuckerman; Ofrat Beyar-Katz (Haematologica)
Not available.